Challenges in implementing industry revolution 4.0 in INDIAN manufacturing SMES: insights from five case studies - N, Suresh; K, Hemamala; N, Ashok (International Journal of Engineering and Technology, 2018)
Purpose-This research examines Small and Medium manufacturing Enterprises (SME’s) awareness, current capability, willingness and ability to identify the challenges involved in implementing Industry 4.0(I 4.0) at their premises. Design/methodology/approach-A set of questionnaire was framed to collect qualitative and quantitative data from five manufacturing SME’s and they were analyzed to gain insight. Findings –3 out of 5 manufacturing SME’s are aware, capable, willing and have ability to identify the challenges for implementing Industry 4.0 at their premises. The study also found that implementation of I 4.0 depends on size of the firm. Medium size manufacturing firms had started investing in Information Technology but small scale industries is still struggling to figure out their long term benefit. Practical implications – The advancement and the integration of the technologies such as Cyber Physical system, Internet Of Things, Artificial intelligence, Big data, Cloud computing and 3D printing provides greater flexibility to the manufacturing firms. In today’s global competition with a huge demand for personalized products at low price with best quality, innovation and capability to full filling batch size of one is becoming important. Hence, to meet the market demand many large-scale industries started investing in advanced technology where SME has yet to pay attention. Originality/value –Paper indicates the Indian manufacturing SME’s preparedness for Industry 4.0. It contains five cases capturing the current manufacturing practices followed in the SME’s and their capability towards implementing Industry I 4.0 in Indian environment.